(untitled) (Bangladesh Journal of Botany, 2025)
An experiment was conducted at the research farm of department of Horticulture, CCS Haryana Agricultural University, Hisar, Haryana to study the effects of foliar application of boron, iron and magnesium on fruit parameters, yield and seed attributes of guava (Psidium guajava L. cv. Hisar Surkha). The experiment consisted of 21 treatments in different combinations of H3BO3, FeSO4 and MgSO4. The results revealed that most of the parameter viz. fruit retention, fruit size, fruit and pulp weight, number of fruits per plant, seed index and yield were noticed superior under treatment T21 (0.5 % of each i.e. boric acid, ferrous sulphate and magnesium sulphate). However, fruit drop and pulp: seed ratios were significantly lowest under the treatment T21. Some of the parameters viz. fruit length: width ratio, fruit colour, pulp colour, specific gravity of guava fruit, seed hardness and total number of seeds per fruit were non-significantly influenced by the nutrient sprays. Bangladesh J. Bot. 54(3): 531-536, 2025 (September)